Evaluating the Accuracy of Recent Type 2 Diabetes Diagnoses in Relation to Glycated Hemoglobin Levels - Akhter, Rehena; Hossain, Mir Mosarraf; Salek, A K M; Qayum, Md Omar; Arslan, Mir Alvi; Islam, Khaleda (Bangladesh Medical Journal, 2025)
Worldwide, the incidence of diabetes mellitus (DM) is rising alarmingly. In 2019, according to International Diabetic Federation (IDF) atlas, Bangladesh was in the 10th position with an estimated 8.4 million diabetic subjects and 56% of them were undiagnosed. If the prevailing situation persists, the number will be increased to 11.4 million in 2030 (and 15.0 million in 2045, occupying the 9th position among countries with high diabetic populations). Early and correct diagnosis with proper management can save people from immense sufferings of DM and its complications. Glycated Hemoglobin (Hemoglobin A1c or HbA1c) level, is a well-recognized marker in the diagnosis and treatment of diabetes. In this study, the cut-off level for HbA1c level was determined in relation to their fasting venous plasma glucose levels of individuals with diabetes and pre-diabetes. This cross-sectional observational study was conducted among 139 newly diagnosed, untreated type 2 diabetic and pre-diabetic individuals who attended Outpatient Departments (OPDs) of Bangabandhu Sheik Mujib Medical University (BSMMU) and Sir Salimullah Medical College Mitford Hospital (SSMC & MH). Type 1 diabetic, patients receiving or received any treatment for diabetes, taking steroids, pregnant, having anemia were excluded from this study. Sensitivity, specificity and the area under the Receiver Operating Characteristic (ROC) curve for HbA1c, using different cut-off values, were calculated considering venous plasma glucose the gold standard test for diagnosis of Diabetes Mellitus. According to the findings of this study, the optimal diagnostic cut-off level of HbA1c was 6.8% with sensitivity 69.81%, specificity 72.73%, positive predictive value 89.02%, negative predictive value 43.21% and accuracy 70.51%. Based on the findings of this study, a larger study involving normoglycemic, newly diagnosed prediabetic and diabetic population, will hopefully determine the cut-off level of HbA1c more accurately to diagnose diabetes and decide the targeted HbA1c in treating diabetes in this population group. This will definitely help diabetic subject, their families and will have a positive impact on society and the country. Bangladesh Med J. 2024 Jan; 53(1): 26-32